Fruitful Packaging : Consumer Preferences Toward Fresh Fruit Packaging for Gift - Azhari, Dimas Ammar; Nasution, Reza Ashari (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. Indonesia is one of the biggest fruit producer country which face low fruit consumption according to WHO. There is this condition where in Indonesia people are more used to consume fruit that they get from someone as a gift. It that can be a potential cause to raise Indonesian fruit consumption. Having a business in packaging design service and production vendor called Boxing Panda, the researchers intended to raise the consumption of fresh fruit in Indonesia by applying a design approach, which is analyzing the ideal product packaging for fruit gift to raise its fame as gift choice. Therefore, the research of customer preference of fruit-gift packaging is essential in knowing what features the customer wanted. Young mid-low Indonesian customer preference in packaging visual elements, informational elements, convenience, eco-efficiency, and packaging inserts were found. The result also in-line with the theory that changing the way a product is packed can affect the sales of the product. Even a low investment in changing the package can drive significant gain in brand sales compared to advertising and promotion activities (Rundh, 2005), this research proven that most people were more convinced to buy fruit if their packaging preferences were met.Â Keywords: marketing, consumer behavior, fruit, gift, packaging